PENGGUNAAN MEDIA PAPAN PENJUMLAHAN BERSUSUN UNTUK MENINGKATKAN KEMAMPUAN DASAR PENJUMLAHAN SISWA KELAS 1 SD - Nadira, Dinda; Saragih, Mandra; Irvan, Irvan; Hadijah, Siti (OMEGA: Jurnal Keilmuan Pendidikan Matematika, 2025)
This study aims to improve the basic addition skills of Grade 1 elementary school students through the use of stacked addition board media. The background of this research is the low understanding of students regarding the concept of addition, as indicated by the learning evaluation results, with a mastery percentage of only 35%. The study was conducted in Grade 1 of UPT SDN 060857 Medan using the Classroom Action Research (CAR) method, which consisted of two cycles. In Cycle I, the use of lecture methods and written exercises did not provide satisfactory results, with a mastery percentage of 65%. Therefore, in Cycle II, improvements were made by implementing stacked addition board media combined with visual videos. The research results showed a significant improvement, with the mastery percentage reaching 90% in Cycle II. The use of stacked addition board media has proven to be effective in helping students understand the concept of addition gradually and in an enjoyable manner. This media not only enhances students' understanding but also increases their engagement and enthusiasm in the learning process.